Gambaran Pengetahuan Ibu Tentang Makanan Bergizi Dengan Kejadian Stunting Pada Balita Di Puskesmas Limapuluh - Ailsha Joya Shafira; Yulnefia Yulnefia (Jurnal Ilmu Kesehatan Abdurrab, 2023)
Backgrounds : Stunting is a condition in toddlers due to long-term, chronic nutritional problems when a z-score value with the body length for age (BLFA) index is less than -2 SD (standard deviation). According to the 2021 Indonesia Nutrition Status Survey data results, the prevalence of stunting in Pekanbaru City is 11,4%. Based on data from the Pekanbaru Public Health Office in 2022, Limapuluh District has the highest prevalence of stunting, with a prevalence of 4,47%. Stunting is caused by many risk factors, one of which is the maternal knowledge of nutritious food. Maternal knowledge about nutritious food is part of the effort to prevent stunting. If stunting is not treated, it will generate short-term and long-term impacts. Objective : To determine the description maternal knowledge about nutritional food and the risk of stunting in toddlers aged 12–23 months at Limapuluh Public Health Center, Pekanbaru City. Method : This is an observational analytics study with a cross-sectional design. This study was conducted in the working area of Limapuluh Public Health Center in Pekanbaru City. The sampling technique used in this study was Proportionate Stratified Random Sampling, with a total sample size of 142 samples. Data analysis was performed through univariate and bivariate analysis with the Chi- Square statistical test. Results : A relationship was found between maternal knowledge of nutritional food and the incidence of stunting in toddlers aged 12-23 months in the working area of Limapuluh Public Health Center in Pekanbaru City with a p-value of 0.000 and a PR value of 8.279. Conclusion : Maternal knowledge about nutritional food is related to and is a risk factor for stunting in toddlers aged 12–23 months in the working area of Limapuluh Public Health Center, Pekanbaru City.